The impact of CFO gender on bank loan contracting - Bill Francis; Iftekhar Hasan; Qiang Wu (Bank of Finland, 2011)
Motivated by recent studies that show female CFOs are more risk averse than male CFOs when making various corporate decisions, we examine whether banks take into consideration the gender of CFOs when pricing bank loans. We find that in our sample, firms under the control of female CFOs on average enjoy about 11% lower bank loan price than firms under the control of male CFOs. In addition, loans given to female CFO-led companies have longer maturities and are less likely to be required to provide collateral than loans given to male CFO led companies. Our results are robust to a series of robustness tests, such as a firm and year-fixed effect regression, a Heckman two-stage self selection model, a propensity score match method and a differences-in-differences approach. Overall, our results suggest that banks tend to recognize the role of female CFOs in providing more reliable accounting information ex ante and reducing default risk ex post, and grant firms with female CFOs lower loan price and more favourable contract terms.
URN:NBN:fi:bof-20140807359
Keywords: 330